2000
DOI: 10.1007/s007690000222
|View full text |Cite
|
Sign up to set email alerts
|

Link to the SI via primary direct methods

Abstract: The possible approaches to realising a link to the SI system and the status of primary direct methods in the traceability chain of chemical measurements are discussed. Some results obtained with the new coulometric standard system are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Once the EP times were estimated using either eWf or TC, the amount of substance of KHP in mol kg −1 was calculated using eq 11. 7,11,27 i t t t i t i t nFmh…”
Section: Coulometric Titrationmentioning
confidence: 99%
“…Once the EP times were estimated using either eWf or TC, the amount of substance of KHP in mol kg −1 was calculated using eq 11. 7,11,27 i t t t i t i t nFmh…”
Section: Coulometric Titrationmentioning
confidence: 99%
“…In this case, the coulometric titration has shown its considerable importance on the HCl concentration determination (Borges et al, 2004). It is worthwhile to point out that the concentration of NaCl was obtained by the gravimetric addition of the salt to the buffer solution (Máriássy et al, 2000), taking into account the purity of the salt, its molecular mass (Lide, 2000) and the water mass fraction of the buffer. The latter is important for the correct calculation of the electrolyte concentration, in mol⋅kg −1…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports regarding a coulometric study for acidimetric standards, [3][4][5][6][7][8] oxidimetric-reductometric standards, [9][10][11][12][13][14] and precipitation standards. [15][16][17][18][19][20][21] Hioki et al reported on the dependence of the coulometric titration results on the amount of sample mass due to the influence by carbon dioxide for acidimetry. 4 Marinenko et al employed constant-current coulometry to determine the amount of chloride ion of NaCl, 15 and to evaluate the stability of NaCl solutions and the influence of the sample forms, solution and solid.…”
Section: 2mentioning
confidence: 99%